2008
DOI: 10.1097/mot.0b013e328303df04
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas preservation for pancreas and islet transplantation

Abstract: Purpose of review To summarize advances and limitations in pancreas procurement and preservation for pancreas and islet transplantation, and review advances in islet protection and preservation. Recent findings Pancreases procured after cardiac death, with in-situ regional organ cooling, have been successfully used for islet transplantation. Colloid-free Celsior and histidine-tryptophan-ketoglutarate preservation solutions are comparable to University of Wisconsin solution when used for cold storage before p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 71 publications
0
26
0
Order By: Relevance
“…UW solution was initially developed for pancreas preservation [31], but was subsequently shown to be excellent also for other abdominal organs [5] as well as islets [11]. Similarly, also celsior and HTK solution have proven valuable in this context [13]. However, despite recent modifications and improvements in islet isolation techniques, it is still often possible to isolate only 50-70% of the total number of islets from a human pancreas [14,15].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…UW solution was initially developed for pancreas preservation [31], but was subsequently shown to be excellent also for other abdominal organs [5] as well as islets [11]. Similarly, also celsior and HTK solution have proven valuable in this context [13]. However, despite recent modifications and improvements in islet isolation techniques, it is still often possible to isolate only 50-70% of the total number of islets from a human pancreas [14,15].…”
Section: Discussionmentioning
confidence: 98%
“…At present, UW solution is the most widely used since it can be applied to all abdominal organs and also, to some extent, for hearts and lungs [1][2][3]5]. Also, HTK solution, initially used for heart preservation with its low potassium content, has proven effective in abdominal transplantations [13]. .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the TLM was reported to achieve better organ function in experimental pancreas [5,6] , heart [7] and intestinal transplantation [8] and to rescue the graft in a model of prolonged warm ischemia time [9] . Higher pancreatic islet yield and better function has been found by several research groups in comparison with conventional UW pancreas storage in experimental [10][11][12] , as well as in clinical studies [13,14] , though this effect has not been confirmed in a larger series [15][16][17] . The TLM for pancreas transplantation has therefore become a standard procedure in several centers supposedly enabling to prolong the cold ischemia time before islet isolation [18][19][20][21] .…”
Section: Introductionmentioning
confidence: 91%
“…During isolation, islets are endangered of mechanical and hypoxic injury which results in excessive oxidative stress and low viability and function. Therefore, methods that can improve islets resistance to oxidative stress are needed to investigate in researches [1][2][3]. Various antioxidant agents like vitamin supplements, herbs, trace elements, and drugs as well as anti-inflammatory drugs have been widely used in different studies to improve function of isolated islets before or after the transplantation [4,5].…”
Section: Introductionmentioning
confidence: 99%